An Online Tool for Misinformation Detection: Enhancing Media Literacy and Critical Thinking Skills - Petko Stefanov Dimov (CV FOUNDAE, 2024)
With the increasing spread of misinformation online, this research focuses on developing a multi-functional tool aimed at enhancing media literacy and critical thinking within online educational environments. The methodology involves a systematic literature review alongside the creation of a practical tool that serves as a 'Swiss army knife' for digital literacy. A key feature of this tool is a structured seven-step verification process for evaluating the credibility of sources, authorship, messages, and the legitimacy of media content. By integrating multiple techniques, this tool allows users to effectively identify and analyze potentially misleading information. The study not only deepens the understanding of disinformation dynamics in educational contexts but also provides an innovative, practical solution to improve media literacy. The tool can be seamlessly integrated into online courses, thus enhancing the overall quality of digital education and fostering a more reliable learning environment.